Analisis Perencanaan Program Pelatihan Life Skill Budidaya Jamur Tiram Untuk Meningkatkan Kewirausahaan - Puteri M, Fira Rama; Meifiana, Sarah Annisa; Sholih, Sholih (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2023)
AbstractEntrepreneurship is a person's ability to create and process his business creatively using the opportunities and resources he has. Through training and empowerment it aims to increase the potential of the community so that their ability can optimally utilize it in entrepreneurship. PKBM Abdi Pertiwi located in Walantaka is one of the institutions that supports this training and empowerment with the oyster mushroom cultivation program. Based on the results of the study using a qualitative descriptive method sourced from primary data of PKBM managers and secondary data of journals and articles. With data collection techniques interview, observation, and documentation. The results of this study show that the planning of the oyster mushroom cultivation program has resulted in its implementation being designed in various stages of planning. The planning of the cultivation training has several stages, namely identifying the Needs and Objectives of the Oyster Mushroom Cultivation Training, identifying the Ease and Obstacles of the Oyster Mushroom Cultivation Training, Determining the Oyster Mushroom Cultivation Training Locations, Preparation of Tools and Materials for the Oyster Mushroom Cultivation Training, OPREC Goals and Process for Cultivation Training Participants Oyster Mushroom, Arranging the Oyster Mushroom Cultivation Training Activity Schedule, and the last stage of Debriefing for the Implementation of the Oyster Mushroom Cultivation Training Program. The planning of the oyster mushroom cultivation program is designed so that the community is able to create their own business in the field of entrepreneurship with life skills training in oyster mushroom cultivation. PKBM Abdi Pertiwi offers and even facilitates the community to improve their skills and independence, especially in the entrepreneurial aspect. This is part of the background of this PKBM which must be supported by all groups as an effort to create skilled and independent human beings to improve the economy in meeting their needs and welfare.Key Words: Cultivation, Oyster Mushrooms, Entrepreneurship, Life Skills, PlanningAbstrakKewirausahaan sebagai kemampuan seseorang menciptakan dan mengolah usahanya dengan kreatif menggunakan peluang dan sumber daya yang dimiliki. Melalui pelatihan dan pemberdayaan bertujuan untuk meningkatkan potensi masyarakat agar kemampuannya dapat secara optimal memanfaatkan digunakan dalam berwirausaha. PKBM Abdi Pertiwi berlokasi di Walantaka ini sebagai salah satu lembaga yang mendukung pelatihan dan pemberdayaan tersebut dengan program budidaya jamur tiram. Berdasarkan hasil penelitian menggunakan metode deskriptif kualitatif bersumber dari data primer pengelola PKBM dan data sekunder jurnal dan artikel. Dengan teknik pengumpulan data wawancara, observasi, dan dokumentasi. Hasil penelitian ini bahwasanya perencanaan program budidaya jamur tiram memperoleh hasil pada pelaksanaannya yang dirancang dalam berbagai tahapan perencanaan. Perencanaan dari pelatihan budidaya memiliki beberapa tahapan yakni diantaranya mengidentifikasi Kebutuhan dan Tujuan Pelatihan Budidaya Jamur Tiram, mengidentifikasi Kemudahan dan Hambatan Pelatihan Budidaya Jamur Tiram, Menetapkan Lokasi Pelatihan Budidaya Jamur Tiram, Persiapan Alat dan bahan Pelatihan Budidaya Jamur Tiram, Sasaran dan Proses OPREC Peserta Pelatihan Budidaya Jamur Tiram, Menyusun Jadwal Kegiatan Pelatihan Budidaya Jamur Tiram, dan tahapan terkahir Pembekalan Pelaksanaan Program Pelatihan Budidaya Jamur Tiram. Perencanaan program budidaya jamur tiram dirancang agar masyarakat mampu menciptakan usahanya sendiri di bidang wirausaha dengan pelatihan life skill budidaya jamur tiram. PKBM Abdi Pertiwi menawarkan bahkan mewadahi masyarakat untuk meningkatkan kemampuan dan kemandirian keterampilan terutama dalam aspek kewirausahaan. Hal tersebut merupakan bagian dari latar belakang PKBM ini berdiri yang harus didukung oleh seluruh kalangan sebagai upaya menciptakan manusia yang terampil dan mandiri untuk meningkatkan ekonomi dalam memenuhi kebutuhan dan kesejahteraan hidupnya.Kata Kunci: Budidaya, Jamur Tiram, Kewirausahaan, Life Skill, Perencanaan